BIOTRANSFORMASI 2E-6E-FARNESOL OLEH KHAMIR ENDOFIT CA1C-4 - Andria Agusta; Yuliasri Jamal (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2011)
The microbial transformation of 2E-6E-farnesol by the endophytic yeast CA1C-4 isolated from temu hitam (Curcuma aeruginosa Roxb.) has been investigated. Incubation of the 2E-6E-farnesol in cultivated endophytic yeast CA1C-4 in PDB at room temperature (25–32o C) under shaking condition at 120 rpm for eight days, produce a biotransformed product. Chemical structure elucidation based on 1H- and 13C-NMR analysis and comparison with published data showed that the biotransformed product is 2E,6E-3,7,11-trimethyl-2,6,10-dodecatrien-1-carboxilic acid.